Computer Application Learning Model Based on Brain Gym to Improve Student Learning Outcomes of PKOM Dehasen University Bengkulu - Mesterjon Mesterjon; Suwarni Suwarni; Diah Selviani (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to produce a brain exercise-based computer application learning model to improve learning outcomes of PKOM students at Dehasen University Bengkulu. This type of research is a development research that produces a learning model based on brain exercise in understanding the concepts of the basics of using Ms. Excel whose syntax is a) introduction, b) core activities include (i) the problem giving phase, (ii) the investigation phase, (iii)) the group discussion phase, (iv) the class discussion phase, (v) the application phase, c) the closing phase. The development design according to Plomp (1999) consists of five phases, namely: initial investigation, design / design, construction / realization, testing, evaluation & revision and implementation. The subjects of this study were students of the first semester of Computer Education at Dehasen University Bengkulu for the 2019/2020 academic year with 18 students. Based on the results of the research, it can be concluded that: 1) from the results of the trials conducted 2 times which were limited trials in this study it can be concluded that all aspects are determined to state that the learning model and all the learning tools developed are practical and effective has been fulfilled then the development cycle to get a practical and effective learning model has ended. But even though all the criteria are met, there are some revisions that must be made to get the final prototype. Revisions made related to the use of language in model books and student activity sheets. After the revision was carried out, a final prototype was obtained, namely a valid, practical, and effective computer-based learning model for brain exercise.